COMMERCIAL MATERIAL TRANSFER AGREEMENT: SALAH SATU SOLUSI PERLINDUNGAN HAK KEKAYAAN INTELEKTUAL PENELITI INDONESIA - Amalia, Marina Eka; Aritonang, Parulian Paidi (UNES Law Review, 2023)
Abstract Currently, Indonesia has not provided adequate protection of intellectual property rights (IPR) in the implementation of the Material Transfer Agreement (MTA). In providing the protection of the Indonesian nation's intellectual property on Genetic Resources (SDG) —especially those derived from genetic material in the form of biological material (DNA/RNA), clinical specimens, and non-biological material (related to human health), the Indonesia's Material Transfer Agreement (MTA) standard is still far from perfect. A Commercial Material Transfer Agreement (CMTA) is required which not only contains clauses on the exchange of genetic material but also contains more detailed provisions on Intellectual Property Rights such as Patents and Benefit Sharing. In this Journal, the author proposes a new framework for the Commercial Material Transfer Agreement (CMTA) which contains additional clauses from the current MTA, which is expected to further protect and encourage of new patentable invention in the future.